Development and Initial Validation of the Attitudes Towards Older Adult Sexuality in Long-term Care Scale (AOASLC). Issue 1 (2nd January 2023) - Spalding, Rachael L.; Katz, Emma; Byers, E. Sandra; Edelstein, Barry
ABSTRACT: In long-term care facilities where older adults may reside, negative attitudes about later life sexuality can result in restrictive facility policies and staff behaviors that suppress residents' rights to sexual expression. No assessment instrument specifically focuses on the sexual behaviors of long-term care residents and existing measures of attitudes toward older adult sexuality do not include sexual expression in long term care, nor do they assess a full range of sexual behaviors. We developed the Attitudes toward Older Adult Sexuality in Long-term Care Scale (AOASLC). A large, diverse sample of 295 community-dwelling adults in the United States completed an online survey through Amazon Mechanical Turk. The survey included the AOASLC and self-report measures of related constructs. Two-hundred-and-ninety-five participants completed the survey ( M age  = 49.16, SD  = 14.69, range = 18– 84 years). Of the sample, 50.2% identified as female, 49.5% identified as male, and one person identified as transgender male. An exploratory factor analysis indicated a two-factor structure. Factor 1 represented general attitudes toward sexual behaviors, and Factor 2 represented acceptability of various sexual behaviors. The instrument evidenced good reliability and validity. While further validation research is necessary, the AOASLC is a promising new measure.